OP29 Long-term dietary patterns are associated with pro-inflammatory and anti-inflammatory features of the gut microbiome. (27th May 2021) - Bolte, L; Vich Vila, A; Imhann, F; Collij, V; Peters, V; Fu, J; Kurilshikov, A; Campmans-Kuijpers, M; Dijkstra, G; Wijmenga, C; Zhernakova, A; Weersma, R
Abstract: Background: The gut microbiome directly affects the balance of pro-inflammatory and anti-inflammatory responses in the gut. As microbes thrive on dietary substrates, the question arises whether we can nourish an anti-inflammatory gut ecosystem. In this study, we investigated the relation between 173 dietary factors and the microbiome of 1425 individuals spanning four cohorts: Crohn's disease, ulcerative colitis, irritable bowel syndrome and the general population. Methods: Shotgun metagenomic sequencing was performed to profile gut microbial composition and function. Dietary intake was assessed through food frequency questionnaires. We performed unsupervised clustering to identify dietary patterns and microbial clusters. Next, linear models were conducted between dietary intake and microbial species and pathways, adding age, sex, caloric intake and sequencing read depth as covariates. Analyses were conducted per cohort, followed by a meta-analysis and heterogeneity estimation. Multiple testing correction was performed on the obtained p-values and a FDR <0.05 was defined as significance cut-off. Results: We identified 38 associations between dietary patterns and microbial clusters. Moreover, 61 individual foods and nutrients were associated with 61 species and 249 metabolic pathways in the meta-analysis across healthy individuals and patients with IBS, Crohn's disease and UC (FDR<0.05, heterogeneity p-value>0.05). Processed foods and animal-derived foods were consistently associated with higher abundances of Firmicutes, Ruminococcus species of the Blautia genus and endotoxin synthesis pathways. The opposite associations were found for clusters comprising fish, nuts, bread and legumes. Moreover, while total plant protein intake was associated with a higher Bifidobacterium abundance (FDR=0.048, coef=4.98), animal-derived protein showed a negative association (FDR=1. 30 x10 -05, coef= -4.1). Lastly, we observed positive associations of fecal calprotectin with a fast food cluster (FDR=4. 14 x10 -4, coef=0.24) and a cluster comprised of high-fat meat, potatoes and gravy (FDR=0.003, coef =0.22), while the opposite was seen for clusters of fish and nuts (FDR=0.038, coef= -0.1) and bread and legumes (FDR=0.005, coef= -2.48). Conclusion: We identified dietary patterns that consistently correlate with groups of bacteria with shared functional roles in both, health and disease. Moreover, specific foods and nutrients were associated with species known to infer mucosal protection and anti-inflammatory effects. A decrease in these bacteria has already been associated with both IBS and IBD. We propose microbial mechanisms through which the diet affects inflammatory responses in the gut as a rationale for future intervention studies.